2013
DOI: 10.1093/eurjhf/hft044
|View full text |Cite
|
Sign up to set email alerts
|

Impact of right ventricular reserve on exercise capacity and survival in patients with pulmonary hypertension

Abstract: AimsPulmonary hypertension is a clinical syndrome characterized by a progressive increase in pulmonary vascular resistance leading to right ventricular failure and death. Pulmonary arterial hypertension (PAH) and chronic thromboembolic pulmonary hypertension (CTEPH) are key subgroups of this disorder with comparable clinical and pathological findings. Resting pulmonary haemodynamics correlate only moderately with functional parameters and do not predict prognosis in these patients sufficiently accurately. We t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
104
2
8

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(117 citation statements)
references
References 26 publications
3
104
2
8
Order By: Relevance
“…Patients with PAH show a typical pattern with a low end-tidal partial pressure of carbon dioxide ( pCO 2 ), high ventilator equivalents for carbon dioxide (VE/ VCO 2 ), low oxygen pulse (VO 2 /HR) and low peak oxygen uptake ( peak VO 2 ) [121]. Several variables determined by CPET provide prognostic information, although peak VO 2 is most widely used for therapeutic decision making [106,[122][123][124][125]. The diagnostic and prognostic information provided by CPET add to that provided by the 6MWT [122].…”
Section: Exercise Capacitymentioning
confidence: 99%
“…Patients with PAH show a typical pattern with a low end-tidal partial pressure of carbon dioxide ( pCO 2 ), high ventilator equivalents for carbon dioxide (VE/ VCO 2 ), low oxygen pulse (VO 2 /HR) and low peak oxygen uptake ( peak VO 2 ) [121]. Several variables determined by CPET provide prognostic information, although peak VO 2 is most widely used for therapeutic decision making [106,[122][123][124][125]. The diagnostic and prognostic information provided by CPET add to that provided by the 6MWT [122].…”
Section: Exercise Capacitymentioning
confidence: 99%
“…Secondly, the study highlights that contractile reserve could be more useful than resting parameters for risk stratification. In a recent study, BLUMBERG et al [31] showed that CI at peak exercise was more strongly associated with outcome than resting parameters. In the present study, CI was increased in the PH group after dobutamine infusion, but to a lesser extent compared with controls.…”
Section: Discussionmentioning
confidence: 97%
“…Even though patients with PAH may present with mild-to-moderate ventilation/perfusion mismatch abnormalities, the main determinant of exercise capacity is right ventricular function (and cardiac output) [31]. In PAH, exercise capacity is dependent on the ability of the RV to respond to the increase in cardiac output required for the metabolic requirements of exercise [32]. Thus, it is perceivable that measures of RV contractile reserve may, therefore, be coupled with exercise capacity.…”
Section: Figurementioning
confidence: 99%